The characteristics of counterattacks in the Spanish league (La Liga) in 2021-2022 - Michailidis, Y.; Papadopoulos, P.; Mandroukas, A.; Metaxas, I.; Metaxas, T. (The Journal of Sports Medicine and Physical Fitness, 2024)
BACKGROUND: Current studies on counterattacks are limited despite the fact that it is one of the most effective ways to score in soccer. The aim of the study was to investigate the characteristics of counterattacks in the Spanish league (La Liga) for the year 2021-2022. METHODS: The sample used in the study were 2631 counterattacks collected from a total of 380 games. The variables used were: 1) the space which the counterattack had started; 2) the number of players who participated; 3) the number of defending players; 4) the duration of the counterattack; 5) the touches to complete the counterattack; 6) the formation of both teams; 7) the way that counterattack was completed (final action); 8) the minute that the counterattack took place; and 9) which team had a home advantage. The results were analyzed using the Chi-square test. The level of significance was defined at P<0.05. RESULTS: Firstly, it appeared that most counterattacks began from the axis of the defensive zone lasting 6-15 seconds. There were 3-4 attackers participating against 4-6 defenders, using 5-9 touches. In addition, most of them took place in the 46-60 minute of the game and were completed in a shot. CONCLUSIONS: The study can help coaches and analysts to understand the characteristics of the counterattacks and adapt their training in a way to make their teams more effective, both in the attacking and defending phase.